2013
DOI: 10.1016/j.chom.2013.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Reassortments Underlie Diverse Influenza H7N9 Genotypes in China

Abstract: Initial genetic characterizations have suggested that the influenza A (H7N9) viruses responsible for the current outbreak in China are novel reassortants. However, little is known about the pathways of their evolution and, in particular, the generation of diverse viral genotypes. Here we report an in-depth evolutionary analysis of whole-genome sequence data of 45 H7N9 and 42 H9N2 viruses isolated from humans, poultry, and wild birds during recent influenza surveillance efforts in China. Our analysis shows that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
117
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 141 publications
(123 citation statements)
references
References 22 publications
4
117
0
Order By: Relevance
“…Later H7N9 isolates were eliminated to better identify the cause of the initial outbreaks because these viruses underwent further gene exchange with local H9N2 viruses during viral transmission after that time point (29). The six internal genes of the H7N9 human isolates grouped closely with those of the recent 2010-2013 H9N2 chicken viruses as shown in previous studies (3)(4)(5), and all belonged to the clades of the G57 genotype ( Fig. 3A and Fig.…”
Section: G57 H9n2 Chicken Virus Provided All Six Of Their Internal Gementioning
confidence: 78%
See 2 more Smart Citations
“…Later H7N9 isolates were eliminated to better identify the cause of the initial outbreaks because these viruses underwent further gene exchange with local H9N2 viruses during viral transmission after that time point (29). The six internal genes of the H7N9 human isolates grouped closely with those of the recent 2010-2013 H9N2 chicken viruses as shown in previous studies (3)(4)(5), and all belonged to the clades of the G57 genotype ( Fig. 3A and Fig.…”
Section: G57 H9n2 Chicken Virus Provided All Six Of Their Internal Gementioning
confidence: 78%
“…Previous studies demonstrate that all six of the internal genes of the novel H7N9 viruses are from H9N2 chicken viruses circulating in China (3)(4)(5). To determine whether these internal genes were all from the clades of G57 genotype viruses, we constructed phylogenetic trees of all internal genes of the available 1994-2013 H9N2 chicken viruses and of the H7N9 human viruses isolated during the first 2 wk of the 2013 H7N9 outbreak.…”
Section: G57 H9n2 Chicken Virus Provided All Six Of Their Internal Gementioning
confidence: 99%
See 1 more Smart Citation
“…However, it is still unknown whether there exists an H9N2 virus using this set of internal genes, as it is unlikely to exhibit fitness in poultry. The estimation of the most recent common ancestor for each virus gene suggested that the H7N9 viruses reassort sequentially 3,11 . Therefore, the recruitment of the internal genes of the H7N9 viruses from H9N2 seems far more complicated than expected.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the NP gene presented a certain divergence, and the strain A/Shanghai/1/2013 is clustered together with A/chicken/ Shanghai/C1/2012(H9N2), rather than the other two H7N9 isolates 3 . Recently, the PB2, PB1, PA and M genes have also been found to form at least two clusters in the phylogenetic trees 10,11 . All these suggest that the H7N9 viruses of this outbreak might be diversified far beyond what we observed from preliminary studies, and consequently a more comprehensive study was called for to uncover the veil of the H7N9 virus.…”
mentioning
confidence: 99%